The association between problematic smartphone use and the severity of temporomandibular disorders: A cross-sectional study - Pei, Ya-Peng; Li, Han-Chao; Zhong, Jia-Wei; Gao, Xin-Lin; Xiao, Chu-Qiao; Yue, Yuan; Xiong, Xin (Frontiers in Public Health, 2022)
Objective: To evaluate the prevalence of different types of temporomandibular disorders (TMD) symptoms in young adults and determine their associations with problematic smartphone use (PSU). Methods: The data of the study were collected from local university students through an online questionnaire survey. Demographic information, Fonseca Anamnestic Index (FAI), Smartphone Addiction Scale – Short Version (SAS-SV), and Patient Health Questionnaire-4 (PHQ-4) responses were gathered electronically and analyzed using multiple logistic regression analysis. Results: There were 163 male and 307 female respondents were participated in this study. The prevalence of PSU and TMD were 83.6% and 66.4%, respectively. There was a moderate statistical correlation between PSU and TMD among young adults (r=0.31, p<0.01). The logistic regression model revealed that the risk of TMD was 1.77 times higher in people with PSU than in those without PSU (OR=1.77 95% CI 1.04-3.06). PSU is a risk factor for pain-related TMD (OR=1.81 95% CI 1.08, 3.04) but not intra-articular TMD. Conclusion: Subjects showed high prevalence of both TMD and PSU. People with PSU experienced more severe and frequent pain-related rather than intra-articular TMD symptoms than those without PSU. By reducing the problematic smartphone use, the risk factor of TMD can be avoided.